Avaliação em larga escala e o trabalho docente: o ENEM em uma escola da rede pública estadual capixaba - Sotta, Marcela Constantino (2020)
This dissertation aimed to analyze the relationship/articulation between Enem and the work of teachers who work in high school at the State School of Elementary and High School Jerônimo Monteiro , located in the south of Espírito Santo. It takes as a the